2019
DOI: 10.1111/jfbc.12961
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects on skin health using polysaccharides from red ginseng by‐product

Abstract: Red Ginseng is well‐known functional food in Asia which is produced by steaming and drying fresh ginseng (Panax ginseng). In the production of red ginseng extract, around 65% of the original material is left over as by‐product and discarded. Most studies on ginseng are focused on ginsenosides. Many functional substances other than ginsenoside are found in red ginseng, but they have not been studied and are usually discarded. Acidic polysaccharides, which are functional polysaccharides found in the by‐product o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 36 publications
0
16
0
1
Order By: Relevance
“…Triterpenoids from Eriobotrya japonica , mainly ursolic, pomolic, colosolic, and methyl colosolic acids, exhibited anti-aging activity by stimulating collagen and hyaluronic acid synthesis [ 22 ]. A plant hormone derived from the jasmonate-induced expression of proteoglycan in the human reconstituted epidermis [ 23 ] and a by-product polysaccharide obtained from red ginseng ( Panax ginseng ) inhibited UV-induced MMP-1 through activator protein-1 (AP-1) [ 24 ]. Finally, ferulic acid improved skin elasticity with significant bleaching, anti-redness, smoothing, and moisturized activity in a clinical study [ 25 ].…”
Section: Skin Anti-aging Natural Products By Acting On the Skin Elast...mentioning
confidence: 99%
See 1 more Smart Citation
“…Triterpenoids from Eriobotrya japonica , mainly ursolic, pomolic, colosolic, and methyl colosolic acids, exhibited anti-aging activity by stimulating collagen and hyaluronic acid synthesis [ 22 ]. A plant hormone derived from the jasmonate-induced expression of proteoglycan in the human reconstituted epidermis [ 23 ] and a by-product polysaccharide obtained from red ginseng ( Panax ginseng ) inhibited UV-induced MMP-1 through activator protein-1 (AP-1) [ 24 ]. Finally, ferulic acid improved skin elasticity with significant bleaching, anti-redness, smoothing, and moisturized activity in a clinical study [ 25 ].…”
Section: Skin Anti-aging Natural Products By Acting On the Skin Elast...mentioning
confidence: 99%
“…AP-1 and its constituent proteins, c-Jun and c-Fos, were activated by UV radiation by an increase in the protein phosphorylation in fibroblasts [ 36 , 37 , 50 ]. Moreover, AP-1 transactivation was increased in response to UV exposure, promoting the skin aging process, since this transcription factor up-regulates MMPs, leading to the degradation of collagen [ 24 ].…”
Section: Skin Anti-aging Natural Products By Acting On Other Signalin...mentioning
confidence: 99%
“…For anxiety disorders, another acidic polysaccharide, WGPA, exhibited an anti-depressant-like effect by affecting social interactions and aggressive behaviors in mice [ 65 ]. For skin health, a byproduct polysaccharide from red ginseng was processed by enzyme-linked high pressure to produce ELHPP-RGBPs, which inhibited the AP-1/MMP-1 pathway and prevented solar ultraviolet-induced skin wrinkles and atopic dermatitis [ 126 ]. The notoginseng polysaccharides PNPS and PNPS-0.5M inhibited a caspase-3 cascade or regulated the alcohol dehydrogenase pathway to protect from cerebral ischemia/reperfusion injury or alcoholic liver damage, respectively [ 43 , 127 ].…”
Section: Biological Activities Of Different Polysaccharides From the Three Speciesmentioning
confidence: 99%
“…Besides, ginseng also produces anti-fatigue activity and reduces lactate dehydrogenase and CPK levels, biomarkers of stress and fatigue. Likewise, experimental evidence showed that the ginseng extract has therapeutic effects with several cardiovascular activities, such as regulating blood circulation, reducing the myocardium size, and improving the lipid profile [4,8,17,22]. This plant exerts anti-adipogenic activity through the modulation of different signaling pathways.…”
Section: Panax Ginsengmentioning
confidence: 99%